Some Results on Fibrewise Topological Spaces
In this paper we define and study new concepts of functions on fibrewise topological spaces over B namely, fibrewise weakly (resp., closure, strongly) continuoac; funttions which are analogous of weakly (resp., closure, strongly) continuous functions and the main result is : Let <p : XY be a fibrewise closure (resp., weakly, closure, strongly, strongly) continuous function, where Y is fibrewise topological space over B and X is a fibrewise set which has the induced fibrewise topology. If for each fibrewise topological space Z, a fibrewise function : z x is weakly (resp., continuous, closure, closure, weakly), then the composition q>O’fl : z Y is weakly (resp.â€¢ weakly, closure, strongly, continuous). Also, we define and study the concepts fibrewise ro-closed (resp., roÂ·coclosed, (i